2017
DOI: 10.1182/blood-2016-05-714329
|View full text |Cite
|
Sign up to set email alerts
|

CSF-1–induced Src signaling can instruct monocytic lineage choice

Abstract: Controlled regulation of lineage decisions is imperative for hematopoiesis. Yet, the molecular mechanisms underlying hematopoietic lineage choices are poorly defined. Colony-stimulating factor 1 (CSF-1), the cytokine acting as the principal regulator of monocyte/macrophage (M) development, has been shown to be able to instruct the lineage choice of uncommitted granulocyte M (GM) progenitors toward an M fate. However, the intracellular signaling pathways involved are unknown. CSF-1 activates a multitude of sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Continuous quantitative long-term single-cell imaging is one way to address this issue and seems predestined to connect asymmetric inheritance with future daughter cell behaviors. 7,40 This technology has already contributed to answering other longstanding questions [41][42][43][44][45][46][47][48][49][50][51] and has been used to quantify fluorescence reporter expression continuously over time, [52][53][54][55][56][57][58] a prerequisite to demonstrate the functional relevance of asymmetrically inherited factors. Using the here-described protocols to reliably detect mitotic hematopoietic cells in fixed samples and live-cell imaging, we just published that the asymmetric inheritance of the cellular degradative machinery, including lysosomes, autophagosomes, mitophagosomes, and NUMB, can predict the fates of daughter cells.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous quantitative long-term single-cell imaging is one way to address this issue and seems predestined to connect asymmetric inheritance with future daughter cell behaviors. 7,40 This technology has already contributed to answering other longstanding questions [41][42][43][44][45][46][47][48][49][50][51] and has been used to quantify fluorescence reporter expression continuously over time, [52][53][54][55][56][57][58] a prerequisite to demonstrate the functional relevance of asymmetrically inherited factors. Using the here-described protocols to reliably detect mitotic hematopoietic cells in fixed samples and live-cell imaging, we just published that the asymmetric inheritance of the cellular degradative machinery, including lysosomes, autophagosomes, mitophagosomes, and NUMB, can predict the fates of daughter cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although cell motility can be restricted by microstructures, extracellular matrix coatings, or stroma cocultures, these solutions have their own drawbacks. [55][56][57] Simple coating with anti-CD43 or anti-CD44 has recently been described to drastically reduce hematopoietic cell motility in vitro without affecting cell behavior. 58 On this coating, cells do not leave the field of view anymore and form 2-dimensional colonies.…”
Section: The Challenge To Image Hematopoietic Cellsmentioning
confidence: 99%
“…Combined loss-and gain-of-function experiments with single-cell tracking demonstrated that Src signaling is sufficient for M-CSF-instructed differentiation of primary GMPs into macrophages. 57 Mechanism of myeloid lineage decisions: the PU.1/GATA-1 switch paradigm…”
Section: Hemogenic Endothelium: Origins Of Hematopoietic Cells In Thementioning
confidence: 99%
“…Time-lapse imaging and in-culture antibody staining was performed as described 12,16,17 in either 384 plates (Greiner) or IBIDI VI 0.4 slides coated at indicated concentrations at 4°C overnight. Cells were segmented and quantified as described.…”
Section: Time-lapse Imagingmentioning
confidence: 99%